The political economy of policy reform - Nelson, D. (Emerald, 2004)
This volume collects the papers from a conference in honor of J. Michael Finger on the occasion of his retirement from the World Bank. The papers cover a number of important issues in the analysis of policy reform and the political economy of policy reform. In particular, papers focus on the political economy of trade liberalization, the role of international agencies in policy reform, policy learning, and the application of economic analysis in policy reform.
Includes index.
Keywords: International economic relations.; Macroeconomics.; elektronické knihy; electronic books